DAMPAK INDONESIA-AUSTRALIA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IA-CEPA) TERHADAP DINAMIKA PEREKONOMIAN INDONESIA MENGGUNAKAN GLOBAL TRADE ANALYSIS PROJECT (GTAP) - , Ariani Dwihastuti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In this study, the researcher wanted to analyze the economic impact of the Indonesia-Australia agreement on the dynamics of the Indonesian economy using Global Trade Analysis Project (GTAP). This study uses data GTAP version 7 in 2008. Database grouped into three commodity sectors and 3 regions/countries. Analyses were performed with the GTAP model to analyze Free Trade Agreement between Australia and Indonesia in the Indonesian economy. This study found that positive effects of the macro-regional cooperation bilateral trade between Australia and Indonesia an increase the trade balance and level of social welfare in the two countries but decreasing in index value of GDP both Indonesia and Australia.